Victoria (Australia) radiotherapy response to working through the first and second wave of COVID‐19: Strategies and staffing. Issue 3 (27th April 2021) - Rykers, Kym; Tacey, Mark; Bowes, Jack; Brown, Kerryn; Yuen, Eva; Wilson, Carlene; Khor, Richard; Foroudi, Farshad
Abstract: Introduction: The COVID‐19 pandemic demanded a rapid response within Radiation Oncology services to minimise the risk of infection to patients and workforce. This study aimed to assess whether the operational changes put in place to reduce infection risks were effective in engaging and supporting staff. Methods: Our service's response saw staff and patients split into morning or afternoon shifts without overlap. Changes included extended clinic hours, modified treatment regimens, expanded online/electronic communication and remote working. Staff were invited to respond to an electronic questionnaire in September 2020, just after the peak of the second COVID‐19 wave in Victoria. Responses captured demographic data, parental status, profession, happiness levels, fear of COVID‐19 and e‐communication efficacy. Results: A 57% response rate was achieved. 69% of respondents were female; 40% were aged 45+ and 35% had school‐aged children. Staff aged 45+ showed a significantly greater fear of COVID‐19 than younger staff. 36% of respondents reported feeling nervous or anxious watching news reports about COVID‐19. 92% of staff were happy with their work arrangements; staff with children were happier than staff without children with their shifts. Online chat/channels were reported as the preferred e‐communication method between colleagues. Conclusion: Staff provided predominantly positive feedback to the changes made in response to the pandemic, reporting high levels of happiness and willingness to continue with the changes implemented during COVID‐19. The strategies adopted worked well and the overall high levels of staff satisfaction will allow our service to quickly pivot should further surges, or another pandemic, arise.